PEMBELAJARAN AL QUR’AN HADITS DI SEKOLAH MIN 4 TANAH LAUT KECAMATAN BATU AMPAR KABUPATEN TANAH LAUT - Hijratul Khair; Imaniah Elfa Rachmah (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2018)
Learning is essentially a process conducted by the teachers and students so that learning occurs in a sense any changed behavior of individual students itself. As for the problems that are discussed in this study of how Learning the Qur'an the Hadith in MIN 4 land sea Stone County Soil Ampar subdistricts of the sea as well as the factors which affected it. This is one of the subject teachers of subjects of the Qur'an the Hadith. As for who becomes the object of this research is the Study of the Qur'an the Hadith on the teaching and learning activities in school MIN 4 Subdistrict land sea Stone Ampar District land sea. source data obtained from one person's teacher subjects the Qur'an the Hadith to obtain the collection of data concerning this research. i.e. by using the techniques of observation, interview and documentation. The data collected is processed by the technique of editing, data classification and interpretation of the data and finally analyzed are descriptive. in taking the conclusions reached through qualitative descriptive method. From the results of this research obtained findings that learning the Qur'an the Hadith in MIN 4 marine land is already well underway. As for the factors that influence in the learning factor is teachers who already have long teaching experience as well as having sufficient educational background support, active student learning and spirit in Al Qur'an Hadith, then the available infrastructure and the environment that is cool and away from air pollution. Keywords: Learning, Hadith, Quran, Madrasah.